1985
DOI: 10.1002/chin.198523280
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND CERTAIN PROPERTIES OF PHOSPHORYLATED FORMALS

Abstract: Es wird eine allgemeine präparative Methode zur Herstellung phosphorylierter Formale mit drei‐ und fünffach koordiniertem Phosphor vorgestellt, die in der Reaktion von Estern und anderen P(III)‐Säurederivaten mit Orthoameisensäureestern besteht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…13 C NMR (100 MHz, CDCl 3 ), δ , ppm: 0.67 (s, 2 Me 3 Si), 14.85 (s, 2Me), 63.97 and 64.08 (both s, 2 CH 2 O), and 98.97 (d, 1 J PC =216.0 Hz, C 1 ). 31 P NMR (162 MHz, CDCl 3 ), δ , ppm: −3.58 (s) (cf ).…”
Section: Methodsmentioning
confidence: 99%
“…13 C NMR (100 MHz, CDCl 3 ), δ , ppm: 0.67 (s, 2 Me 3 Si), 14.85 (s, 2Me), 63.97 and 64.08 (both s, 2 CH 2 O), and 98.97 (d, 1 J PC =216.0 Hz, C 1 ). 31 P NMR (162 MHz, CDCl 3 ), δ , ppm: −3.58 (s) (cf ).…”
Section: Methodsmentioning
confidence: 99%
“…First phosphorylated formaldehyde acetals 13 were obtained by the reaction of hydrophosphinoyl compounds 51 – 53 with orthoformate esters 54 on heating. The reaction with dialkyl phosphites 51 [19,75] is conducted by heating to 182 °C [76,77] or at 60 °C in the presence of BF 3 ·Et 2 O as catalyst (without the catalyst the yields decrease from 69%–90% to 25% [75]). In the case of sec -phosphine oxides—dialkylphosphine oxides 52 [77] and diphenylphosphine oxide 53 [77,78], the reaction proceeds at 100 °C [19,77].…”
Section: Chemistry Of Phosphorylated Formaldehyde Derivativesmentioning
confidence: 99%
“…Compounds 33 can be also prepared by the reaction of trialkyl phosphites 58 with orthoformate esters 54 . It was shown that phosphites 58 do not react directly with 54 even on heating [19]. However, as in the case of dialkyl phosphites 51 , orthoformates 54 react with trialkyl phosphites 58 and their analogs (AlkO) 2 POX 59 , where X = Me 3 Si, (AlkO) 2 P, (AlkO 2 )P(O) on heating in the presence of catalytic amounts of boron trifluoride etherate BF 3 ·Et 2 O [19].…”
Section: Chemistry Of Phosphorylated Formaldehyde Derivativesmentioning
confidence: 99%
See 2 more Smart Citations